Analyzing Image Files for Modification - Wood, Mitchell D.; Sherman, Conor J.; Leitzke, Taren J. (My University, 2013)
The availability of tools such as PhotoShop and Gimp has allowed people to easily create high quality, subtle changes to images. Automatic detection of "photo shopped" images can be useful to anyone who is skeptical of the validity of media sources. Photoshopped images, as they pertain to the media, damage the integrity of the news source that uses them. The purpose of this study was to design a program that detects intentional modifications in photographs.
Color poster with text and images.
Keywords: Images, photographic; Photography--Digital techniques; Computer programs; Posters